Inducing a Mucosal Barrier–Sparing Inflammatory Response in Laboratory‐Grown Primary Human Nasal Epithelial Cells. Issue 1 (4th February 2019) - Ramezanpour, Mahnaz; Bolt, Harrison; Psaltis, Alkis; Wormald, Peter‐John; Vreugde, Sarah
Abstract: Here we use the toll‐like receptor (TLR) 3 agonist poly I:C (LMW) to induce an inflammatory response in cells of submerged and/or air‐liquid interface (ALI) cultures of human nasal epithelial cells (HNECs). The inflammatory response is determined by measuring interleukin‐6 (IL‐6) protein levels by enzyme‐linked immunosorbent assay (ELISA). The mucosal barrier integrity is determined by measuring transepithelial electrical resistance (TEER) and passage of fluorescently labeled dextrans. Stimulation with poly (I:C) LMW induces a 15‐ to 17‐fold increase in IL‐6 production by HNEC‐ALI cells. © 2019 by John Wiley & Sons, Inc.